A multiple-perspective approach for the assessment and learning of ultrasound skills - Tolsgaard, Martin Grønnebæk (Perspect Med Educ, 2018)
Ultrasound has become a core skill in many specialties. We evaluated the learning and assessment of ultrasound skills in Obstetrics-Gynaecology in a series of eight studies. In the clinical setting, we found that trainees as well as experienced clinicians struggle with technical aspects of performance such as image optimization. We examined how to improve these aspects of performance in the simulated setting by determining mastery learning levels and exploring learning curves for novices. We then examined how to improve the efficiency of training as well as transfer of learning through the use of dyad practice as compared with single practice. We found that the use of simulation-based training focusing on technical aspects of performance in addition to clinical training led to sustained improvements in performance after two months of clinical training in all aspects of performance. In addition, we found an interaction effect between initial simulation-based training and subsequent clinical training on trainees’ need for supervision. These findings suggest that simulation-based training can work as preparation for future learning rather than merely as added learning. Finally, we found that the use of simulation-based initial training led to a large decrease in patients’ discomfort, improvements in their perceived safety and confidence in their ultrasound operator. However, simulation-based training comes at a cost and in the final study we developed a model for conducting cost-effectiveness studies and provided data from an example study on how to link training costs with quality of care.